Choroidal thickness and axial length changes in myopic children treated with orthokeratology. Issue 6 (December 2017) - Li, Zhouyue; Cui, Dongmei; Hu, Yin; Ao, Sichun; Zeng, Junwen; Yang, Xiao
Abstract: Purpose: To analyze the change in subfoveal choroidal thickness (SFChT) and its relationship with changes in axial length (AL) in myopic children treated with Orthokeratology (Ortho-k). Methods: Fifty myopic children participated in this study: 29 subjects were treated with Ortho-k lenses and 21 with single vision distance spectacles. The SFChT and ocular biometrics, including AL, were measured at baseline, one month, and six months after lens wear in both groups. Results: AL significantly increased in both groups over time. In the Ortho-k group, SFChT also increased; however, there was no significant change in SFChT in the control group over time. At the six-month visit, the magnitude of eye growth was significantly reduced in the Ortho-k group compared to the control group (0.06 ± 0.10 mm vs. 0.17 ± 0.10 mm, P < 0.001). SFChT was significantly thicker in the Ortho-k group compared to the control group at the one-month and six-month visits (15.78 ± 11.37 μm vs. −2.98 ± 8.96 μm, P < 0.001 (one-month visit); 21.03 ± 12.74 μm vs. −2.50 ± 14.43 μm, P < 0.001 (six-month visit)), although there was no significant difference between the two follow-up visits (P = 0.102 for the Ortho-k group; P = 0.898 for the control group). Changes in the large choroidal vascular layer (LCVL) accounted for the majority of subfoveal choroidal thickening (approximately 77% and 80% at one-month and six-month visits, respectively). Conclusion: Ortho-k treatment induced significant choroidal thickening and a slowing of eye growth. LCVL thickening accounted for the majority of SFChT thickening. However, its potential mechanism in myopia control requires further investigation.